Images de Pompéi - Desrochers, Brigitte (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2000)
This article outlines the history of representations of Pompeii, from the discovery of the site in 1748 to the present day. It ties artistic interpretations to the development of archaeological research, changing forms of patronage, and evolving audiences.Initially, images of Pompeii were produced under Royal patronage. As soon as the site became known across Europe, adventurers took it upon themselves to produce different kinds of views, intended for armchair travelers. Come the industrial revolution, and these representations split into two broad categories: tourist views, responding to market forces on the one hand, and state-sponsored, scientific surveys on the other.These changing forms of patronage influenced the aesthetic sensibilities of the images. The Bourbons wanted the images of Pompeii to contribute to their glory; adventurers cast a much more disinterested gaze at their subject matter; and scientists sought to achieve something of a subjective self-erasure, as it were, in their pursuit of a purely objective reading of the ancient city.Pictorial composition reflected these changing attitudes. Initially, objects looked like jewels, carefully enshrined inside the picture frame. As time passed, the objects were gradually related back to their original context. Background elements could be seen, and functional connections were made evident. The city finally appeared entire, reading as an organic unity connected to the landscape. Scientists pushed the process even further, pulverizing the city into multiple layers of statistical information.